The Ghost of Disruption: Preventing Business Death with Organizational Culture and Engaging Artificial Intelligence - Primadona Primadona; Dyah Eko Setyowati; Duta Mustajab; Yudith Dyah Hapsari; Muhammad Taufan Ashshiddiqi (Universitas Dharma Wacana, 2022)
Organizational Identity (OI) as part of organizational culture refers to Organizational Change in organizational characteristics which in the eyes of its members are the center of the organization's character or